Digital technologies in early and preschool education - Giorgadze, Tinatin (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Today, the role of digital technologies in early and preschool education has increased significantly. Observations show that children use tablets or interactive whiteboards for learning and playing with joy and enthusiasm. These technologies create new opportunities for personalized and interactive learning. Through digital resources, children not only hear stories, but also interact with characters, which further develops their imagination and language skills. The article presents the results of the research, which present various aspects of the integration of digital technologies in the teaching-learning process: both benefits and threats. It also shares recommendations based on the results of studies of successful practices.